(untitled) (Zoological Archives: An International Journal, 2026)
Seasonal migration in birds and other vertebrates requires precise coordination of physiological transitions – gonadal development, hyperphagia, fuel deposition, and moult – with environmental cues including photoperiod, temperature, and food availability, involving epigenetic mechanisms that enable rapid, reversible, and potentially heritable adjustments of gene expression without changes in DNA sequence. This study characterised genome-wide DNA methylation dynamics (WGBS; 18.4x coverage), histone modification patterns (ChIP-seq for H3K4me3 and H3K27me3), and small RNA profiles (sRNA-seq) across four seasonal physiological states (pre-migratory, migratory, wintering, pre-breeding) in 42 individuals of three long-distance migratory bird species – European reed warbler (Acrocephalus scirpaceus), common swift (Apus apus), and barn swallow (Hirundo rustica) – compared to three non-migratory resident species (house sparrow Passer domesticus, great tit Parus major, European robin Erithacus rubecula; 42 individuals each). Total 2,840 epigenome profiles generated (2021-2024). Migratory species showed 2.84-fold more differentially methylated regions (DMRs) between seasonal states than resident species (mean 2,840 +/- 484 vs. 1,024 +/- 248 DMRs per species per transition; p < 0.001). Pre-migratory state-specific hypomethylation concentrated at promoters of fatty acid metabolism genes (FABP4, FASN, CPT1A) and circadian clock genes (CLOCK, ARNTL, PER2), while migratory state hypermethylation concentrated at gonadal development regulators (GNRHR, LHB, CYP19A1). H3K4me3 peaks at metabolic gene promoters increased 3.84 +/- 0.84-fold during hyperphagia vs. wintering. A Migratory Epigenetic Plasticity Index (MEPI) integrating DMR count, methylation amplitude, and state specificity predicted individual migration distance with r = +0.74 (p < 0.001), suggesting that epigenetic plasticity capacity is positively associated with migratory range.